Prototipe User Interface Telepsikologi Layanan Kampus Yang Terintegrasi Sistem Big Data Kesehatan - Astuti, Nina Dwi; Fahyudi, Asharul; Naryanti, Indah; Sugiarti, Ida; Sukawan, Ari (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2025)
Counselling services are an important component of higher education service delivery. Poltekkes Kemenkes Semarang provides counselling services; however, consultation outcomes have not yet been integrated into the clinic’s Electronic Medical Records (EMR), resulting in incomplete patient examination histories and difficulties for psychologists in delivering care. Therefore, the development of an EMR-integrated telepsychology system is required. This study aims to develop a telepsychology prototype integrated with EMR using a prototyping research method. Informants included clinic managers, administrative staff, and psychologists. The research stages comprised information system requirements analysis, data requirements analysis, and user interface design. The telepsychology user interface prototype was developed using Figma. The results show that the developed prototype is able to meet user needs, particularly by enabling psychologists to access psychological examination data efficiently. The telepsychology system supports online counselling services and allows psychologists to view complete patient examination histories directly through the system. In addition, telepsychology records can be accessed by general practitioners as supporting information for referral decisions to psychiatrists. The Primary Clinic of Poltekkes Kemenkes Semarang is encouraged to further enhance the telepsychology application by improving video call features and providing mental health information and self-care tips to support campus clinic services.